Lysosome exocytosis as a therapeutic target to impair breast cancer progression - Rodrigues, Ana Rita Vieira Lourenço Henriques (2024)
Breast cancer (BC) is the most frequently diagnosed type of cancer and the second leading cause of cancer-related deaths in women, with metastasis contributing substantially to poor prognosis. Metastasis formation involves acquisition of migratory and invasive capacities by cancer cells, allowing them to form secondary tumors. Previous studies indicate that lysosome exocytosis is upregulated in BC cells, leading to alterations in the tumor microenvironment and degradation of the extracellular matrix, creating favorable conditions for tumor invasion. This project investigated the role of lysosome exocytosis in BC cell invasion. For this, we modulated key regulators of this pathway, namely RAB7A, the RAB7A effector RILP, and RAB10. Moreover, we modulated lysosome exocytosis with pharmacological compounds, including ML-SA1. We found that the silencing of RAB7A, a crucial regulator of lysosomal trafficking, increased lysosome exocytosis and invasion of both highly invasive MDA-MB-231 and poorly invasive MCF-7 BC cell lines. Conversely, the silencing of RILP, which mediates retrograde transport of lysosomes, as well as late endosome-lysosome fusion, resulted in decreased lysosome exocytosis and invasion of highly invasive MDA-MB-231 cells. Similarly, RAB10 silencing led to reduced lysosome exocytosis and invasion of MDA-MB-231 cells. Additionally, treatment of poorly invasive MCF-7 cells, with ML-SA1 increased both lysosome exocytosis and invasion. Overall, our results show that modulating lysosome exocytosis positively impacts invasive behavior in BC cells, demonstrating a clear causality between lysosome exocytosis and BC cell invasion. This suggests that targeting lysosome exocytosis could be an effective therapeutic strategy to impair BC cell invasion and tumor progression. Future research should focus on exploring pharmacological inhibitors of lysosome exocytosis, towards the impairment of BC cell invasion, to enhance treatment efficacy and improve patient prognosis.